Effect of Chelated Calcium Proteinate Fed in the Maternal Diet of Turkey Breeders on Embryo Cardiac Physiology and Poult Quality - Christensen, V.L.; Grimes, J.L.; Rowland, R.D.; Ort, D.T. (International Journal of Poultry Science, 2006)
Embryo and hatchling survival diminish as turkey breeder hens age. Recent data indicated that a chelated calcium proteinate (CCP) additive given to turkey breeder hens improved embryo survival as hens aged but did not affect shell thickness. We hypothesized that the mechanism by which this occurred may be by improved functional shell quality and its consequent effect on cardiac physiology. To test the hypothesis, CCP was supplemented to the diet of Large White turkey breeder hens for a 25 week egg production period and compared with controls without supplementation. Eggshell conductance, conductance constants, poult growth and cardiac physiology were measured at weeks 10, 18 and 25 of production. Because elevated temperatures increase heart rates and reduce heart weight and survival, half of the eggs was incubated at 37.9°C whereas the remaining eggs were incubated at 37.5°C. Embryos and poults from the CCP group exhibited increased heart weights and improved cardiac health. The hatching poults from CCP-fed hens also grew faster for the first 3 d of life. We conclude that CCP improves eggshell conductance, and the subsequent eggshell conductance constant (k) of eggs from turkey breeder hens. The change in k improved embryo cardiac health and poult BW after hatching.